Dosa Ketidakpedulian sebagai Kekerasan Pasif: Analisis Etika Kontemporer terhadap Sikap Edom dalam Obaja 1:10-14 - Deavy Stanley Tumuju; Unggun Maradona (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study aims to examine Obadiah 1:10-14 exegetically in order to show that Edom's indifference to Judah's suffering was a form of passive violence that in the perspective of Old Testament ethics was understood as sin, while actualizing its meaning for the social context and life of the church today. Very rarely has research examined apathy as a major sin, read Edom's actions as a form of passive violence, or developed a category of prophetic ethics based on